2015
DOI: 10.1016/j.celrep.2015.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Tetracyclines Disturb Mitochondrial Function across Eukaryotic Models: A Call for Caution in Biomedical Research

Abstract: Summary In recent years, tetracyclines, such as doxycycline, have become broadly used to control gene expression by virtue of the Tet-On/Tet-Off systems. The wide range of direct effects of tetracycline use has, however, not been fully appreciated. We show here that these antibiotics induce a mitonuclear protein imbalance through their effects on mitochondrial translation, an effect that likely reflects the evolutionary relationship between mitochondria and proteobacteria. Tetracyclines, Even at low concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
374
5
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 404 publications
(397 citation statements)
references
References 42 publications
15
374
5
3
Order By: Relevance
“…A recent publication highlighted the possible impact of doxycycline on mitochondrial gene expression (40). In our experiments, we included doxycycline-treated controls for both the in vivo ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication highlighted the possible impact of doxycycline on mitochondrial gene expression (40). In our experiments, we included doxycycline-treated controls for both the in vivo ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given the tight link between the UPR mt and AD observed above, we investigated the effects of two established strategies to induce the UPR mt in C. elegans ; genetically, by silencing the expression of the mitochondrial ribosomal protein mrps-5 23 , and pharmacologically, by using the mitochondrial translation inhibitor doxycycline (dox) 23,24 . Both interventions, which favor worm health and lifespan 23 , markedly induced transcripts of UPR mt , mitophagy and respiration genes in GMC101 (Fig.…”
Section: Reducing Mitochondrial Translation Lowers Aβ Proteotoxicitymentioning
confidence: 99%
“…Auwerx and colleagues (Chatzispyrou et al 2015;Moullan et al 2015) demonstrated that doxycycline negatively impacts mitochrondrial function. Doxycycline can also impact the gut microbiota in humans; the direct impact of this on adipose biology is unclear but potentially significant (Angelakis et al 2014).…”
Section: Perspectives Limitations and Future Directionsmentioning
confidence: 99%